Changes in yields and volatile oil composition of fennel (Foeniculum vulgare Mill.) in high plant populations - Özel, Abdulhabip; Koşar, İslim and Demirbilek, Tuncay and Erden, Kaan (Italian Journal of Agronomy, 2019)
This research was managed to identify the effects of the different seed quantity (5, 10, 15 and 20 kg.ha–1) and row interval (15 and 30 cm) on the yields and the volatile oil components of fennel (Foeniculum vulgare Mill.) under the Harran Plain conditions, during 2013 and 2014 years. The study was established according to the split plot in randomised complete block design. Seed and volatile oil yields, volatile oil ratio and volatile oil components were importantly affected seed quantity and row interval. The transaction of 15 cm × 10 kg.ha–1, the highest seed and volatile oil yield were taken, was determined to be the most suitable. The trans-anethole was taken the primary component under all transactions and it was changed to depend on the row interval and seed quantities.